2022
DOI: 10.35794/emba.v10i2.39745
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS ENTREPRENEURIAL SELF-EFFICACY PADA PENGUSAHA BIDANG FOOD&BEVERAGE DI MALALAYANG.

Abstract: Pertumbuhan UKM di Indonesia diperlukan agar UKM menjadi tumpuan untuk memperluas lapangan perkerjaan dan pemerataan untuk meningkatan pendapatan masyarakat, serta mendorong pertumbuhan ekonomi. Oleh sebab itu UKM khususnya Industri F&B di Manado semakin hari semakin berkembang yang artinya bisnis kuliner merupakan bisnis yang menjanjikan di Kota Manado, sehingga dibutuhkan Etrepreneurial Self-Efficacy terhadap Pengusaha tersebut. Penelitian ini bertujuan untuk menganalisa tentang Entrepreneurial Self-Effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…This is in line with the view of Jailani (2017) argues that a person's level of interest in entrepreneurship is mostly determined by their amount of entrepreneurial motivation. The findings of this study are consistent with those of (Mentang et al, 2022), who found that interest in entrepreneurship was influenced by both entrepreneurial expertise and motivation. The findings of Lubis, (2018) study corroborate this finding, demonstrating that entrepreneurship education substantially impacts entrepreneurial motivation.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…This is in line with the view of Jailani (2017) argues that a person's level of interest in entrepreneurship is mostly determined by their amount of entrepreneurial motivation. The findings of this study are consistent with those of (Mentang et al, 2022), who found that interest in entrepreneurship was influenced by both entrepreneurial expertise and motivation. The findings of Lubis, (2018) study corroborate this finding, demonstrating that entrepreneurship education substantially impacts entrepreneurial motivation.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…The growth of SMEs in Indonesia is very important for Indonesia's economic growth, therefore SMEs must be encouraged to grow so that they become a focus for expanding employment and equity to increase people's income, and encourage economic growth. In this case, people who are diligent and confident are needed to run a business, and these people are business people or also called business people (Mentang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%